Anti-polymorphonuclear neutrophil antibodies in patients with leukopenia or neutropenia - Riera Cervantes, Norma Edith (2010)
Introduction: Immune humoral neutropenia (Np) could be the consequence of anti-polymorphonuclear neutrophil (PMN) antibodies, circulating immune complexes (CIC) and/or antibodies against myeloid precursors. Granulocyte immunofluorescence test (GIFT) and a leukoagglutination technique (LAGT) assays are recommended for its diagnosis. Methods: Fifty adult patients with secondary Np were screened for anti-PMN. GIFT by flow cytometry from viable PMN and LAGT were employed. In addition, CIC levels, low expression of CD16b (CD16 blow), PMN phenotype and sera tumor necrosis factor- alpha (TNF-α) were also evaluated. Results: Direct IgG-PMN binding (dir-GIFT) was positive in 16% of the patients. Antibodies against autologous PMN were detected in 32% of the samples by indirect (ind)-GIFT and demonstrated in 70% of the sera by both ind-GIFT and/ or LAGT. Predominance of human neutrophil alloantigen (HNA)-1b and HNA-2 expression was confirmed. CD16b low was detected in 16% of the patient's PMN and TNF-α in 68% of sera patients. Conclusion:Our results suggest that diagnosis of immune Np in the laboratory may be improved by focusing on patient's PMN together with the assessment of cellular markers. © 2009 Blackwell Publishing Ltd.